The impacts of hydropower dam construction on the adjacent rural households' food insecurity in Northwestern Ethiopia - Yeshi Jima; Dawit Diriba Guta; Feyera Senbeta; Belay Simane (Cogent Economics & Finance, 2022)
This study examines the impact of two hydropower dam reservoirs, Amerti and Neshe, on the adjacent rural household food insecurity in the Abay Chome district, northwestern Ethiopia. A cross-sectional method was employed to collect data from 485 households (268 affected and 217 non-affected households) following a probability proportional to the size sampling procedure. Households' food insecurity access scale (HFIAS) and households' dietary diversity score (HDDS) were used to examine households' food insecurity status in the study area. The Endogenous Switching Regression model was employed to identify the impact of the dam construction on household food insecurity. The results revealed that the average HDDS and HFIAS in the study area were 5.1 and 10.29, respectively. The study also demonstrated that the affected household's average HDDS and HFIAS were 4.48 and 10.98, respectively. The study results further revealed that the construction of dams has significantly increased the HFIAS of displaced households by 14.6% while reducing HDDS by 24%. This study found a negative relationship between dam construction and food security, although dam construction is supposed to increase food security by increasing access to water. Thus, we recommend that hydropower reservoirs be effectively designed to reduce the impacts on adjacent communities.
Keywords: 330; development; food insecurity; households; hydropower dams; landlessness